Analisis Perbandingan Strategi Pengisian Ulang pada Masalah Electric Vehicle Routing Problem with Time Windows (EVRPTW): Studi Kasus Layanan Ekspedisi - Ade Aisyah Arifna Putri; Haryanto, Zelania In Haryanto (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2025)
The growing market share of electric vehicles in Indonesia aligns with the government's initiatives to reduce greenhouse gas emissions and promote the adoption of electric vehicles to 30% of the total vehicle fleet by 2035. The constrained range of electric vehicles and the need for charging station accessibility present difficulties to efficient route planning. This study examines the Electric Vehicle Routing Problem with Time Windows (E-VRPTW), taking into account consumer demands and time constraints. Two battery charging strategies are assessed: full recharge (EVRPTW-FR) and partial recharge (EVRPTW-PR), employing the nearest neighbor heuristic algorithm for route optimization. The result indicates that the partial recharge strategy generates a lower total cost than the full recharge strategy, reaching a cost reduction of 13.14%. The partial recharge strategy requires fewer vehicles to serve all customers, thus lowering vehicle investment costs.